My Mosque, My Business Hub: The Mediating Power of Product Innovation in Mosque Based SME Performance - Asmayanti Asmayanti; Hajar Dewantara; Andi Reski Nurhikmah; Aminuddin Hamdat; Andika Isma (Fundamental and Applied Management Journal, 2026)
This research investigates mosque-based entrepreneurship and the mediating role of product innovation on business performance in Indonesia. The study highlights the significant contribution of entrepreneurship to economic growth, while noting challenges faced by SMEs in Indonesia, such as access to capital and intense competition. The research aims to assess the implementation of mosque-based entrepreneurship and how product innovation can enhance business performance, measured through profitability, productivity, and market share. The quality of service and human resources are also examined for their impact on business performance and product innovation. Data was collected through questionnaires from 425 mosque SMEs in Indonesia and analyzed using Partial Least Square (PLS). The findings show that service quality and human resources positively influence business performance, both directly and through product innovation. This study underscores the importance of innovation in improving competitiveness and the performance of SMEs.